Pemanfaatan Media Interaktif sebagai Inovasi Pembelajaran Sejarah di Sekolah Menangah - Nabila Septiana; Suhendro Suhendro; Pahmi Kurniawan; Syarifuddin Syarifuddin; Rani Oktapiani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study is based on the fact that history learning in secondary schools is still dominated by a memorization-based approach, which does not fully encourage deep understanding or interest in learning among students, while the characteristics of the digital generation demand more interactive, visual, and participatory strategies. This study aims to examine the urgency of utilizing interactive media in history learning, identify relevant forms of media, and explain their implications for the quality of the learning process and outcomes. The method used is a literature study examining various recent studies on the use of interactive multimedia, digital e-books, historical videos and simulations, and educational games in history learning. The results of the study show that the use of interactive media contributes to increasing interest and motivation in learning, strengthening understanding of concepts and the chronology of events, and developing students' critical and historical thinking skills, while encouraging a shift in the role of teachers to become facilitators and innovators of learning. Therefore, its integration needs to be designed in a targeted and contextual manner to be in line with the characteristics of students and the demands of 21st-century learning.